Urban Air Mobility (UAM) (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
The beginning of the 2020s finds connected multimodality at the forefront of urban mobility transformation. Cities grow larger and increasingly face problems caused by transport and traffic. It is expected that Europe's population in urban areas will increase from today's 74% to about 83.7% in 2050. Congestion costs nearly 2% of the EU’s GDP annually, while 85% of the EU’s urban population is exposed to fine particulate matter (PM2.5) at levels deemed harmful to health. To face this challenge, cities increasingly strive to implement SUMPs (Sustainable Urban Mobility Plans) to increase the quality of life in their areas and encourage economic growth. Meanwhile, Urban Air Mobility (UAM) offers a promising opportunity to mitigate road (surface) congestion by integrating an additional modality or dimension into the urban mobility landscape. Nonetheless, on the path to fully urban operations of capable automated autonomous aircraft and integrated UAM services, plenty of questions remain open.